ANALISIS PERLAKUAN AKUNTANSI TERHADAP RESTRUKTURISASI KREDIT BERMASALAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG MANADO - Brigita, Waworuntu Gicella; Ilat, Ventje; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Many creditors have difficulty in returning the bank. Therefore, it is necessary to restructure non-performing loans to minimize outstanding loans. Credit restructuring is an effort used by banks in credit business activities to enable the debtor to fulfill its obligations. Similarly, the Commercial Bank in North Sulawesi, namely PT. Bank Rakyat Indonesia (Persero) Tbk branch Manado which is one of the main activities to provide credit to customers. The largest revenue in PT. Bank Rakyat Indonesia (Persero) Tbk branch Manado comes from loan interest to debtor. From the results of the study, there are still arrears that have congestion. However, PT. Bank Rakyat Indonesia (Persero) Tbk branch Manado has been conducting a restructuring of non-performing loans. This study was conducted with the aim to know and analyze the accounting treatment that is, recognition, measurement, and disclosure to the restructuring of problem loans at PT. Bank Rakyat Indonesia (Persero) Tbk branch Manado. The using methods of the observation is qualitative analysis methods. The results showed that PT. Bank Rakyat Indonesia (Persero) Tbk branch Manado has implemented the appropriate restructuring procedures in accordance with the applicable regulations. Keywords: Restructuring, problem loans